The joy of C Programming in C - Miller, Lawrence H. (John Wiley & Sons, 1986)
This step-by-step companion takes the reader on a journey from novice to expert C programmer. Written in a very friendly tone, this book really is a joy to read. Numerous case studies, complete, detailed examples, and "warnings" on potential trouble spots provide additional support for the students. Examples use carefully selected programs similar to ones the reader may have encountered in another language, easing the transition to programming in C. The complete code for program examples illustrate the language in a realistic way and their thoroughness enables the reader to avoid potentially confusing program fragments. The last part of the text deals with real world issues such as external files, advanced data structures, portability and efficiency and moving from programming in C to programming in C++. Case studies provide a real world application that cements the concepts covered in other chapters. The book contains chapter summaries listing the most important language features covered in the chapters along with crucial details of their use